Insights into possibilities for grouping and read-across for nanomaterials in EU chemicals legislation. Issue 1 (2nd January 2019) - Mech, A.; Rasmussen, K.; Jantunen, P.; Aicher, L.; Alessandrelli, M.; Bernauer, U.; Bleeker, E. A. J.; Bouillard, J.; Di Prospero Fanghella, P.; Draisci, R.; Dusinska, M.; Encheva, G.; et al.
Abstract: This paper presents a comprehensive review of European Union (EU) legislation addressing the safety of chemical substances, and possibilities within each piece of legislation for applying grouping and read-across approaches for the assessment of nanomaterials (NMs). Hence, this review considers both the overarching regulation of chemical substances under REACH (Regulation (EC) No 1907/2006 on registration, evaluation, authorization, and restriction of chemicals) and CLP (Regulation (EC) No 1272/2008 on classification, labeling and packaging of substances and mixtures) and the sector-specific pieces of legislation for cosmetic, plant protection and biocidal products, and legislation addressing food, novel food, and food contact materials. The relevant supporting documents (e.g. guidance documents) regarding each piece of legislation were identified and reviewed, considering the relevant technical and scientific literature. Prospective regulatory needs for implementing grouping in the assessment of NMs were identified, and the question whether each particular piece of legislation permits the use of grouping and read-across to address information gaps was answered.